Prosedur Psikotes untuk Kesiapan Mental Pengguna Senjata Api di Polda Sumsel - Hurriyati, Dwi; Sivtalia, Peny; Hardiyono, Bayu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The use of firearms is a high-risk task for police officers. Therefore, they need to be mentally prepared to be able to carry out their duties properly and safely. One of the efforts to improve the mental readiness of Polri members is by conducting psychological tests. This report aims to present in-depth information about the psychological test procedures that have been implemented at the South Sumatra Police in the context of the mental readiness of firearm users. The method of collecting data through questionnaires, the results of community service, and the implementation of psychological test procedures to assess the cognitive readiness of firearm users at the South Sumatra Police requires a holistic and well-planned approach. The first step is to thoroughly understand the purpose of the psychological test, which includes identifying potential mental problems, assessing the ability to control emotions, and measuring an individual's psychological stability. Furthermore, the selection of tests should take into account the local, cultural, and task context of firearm users so that the results are relevant and can be interpreted appropriately. Test validity and reliability are also key in ensuring the accuracy of the results by testing and validating the tests regularly.